The anti-PD-1 era of cervical cancer: achievement, opportunity, and challenge - Li, Chen; Cang, Wei; Gu, Yu; Chen, Lihua; Xiang, Yang (Frontiers in Immunology, 2023)
Cervical cancer is one of the three major female gynecological malignancies, becoming a major global health challenge. Although about 90% of early-stage patients can be cured by surgery, advanced-stage patients still need new treatment methods to improve their efficacy, especially for those with recurrence and metastasis tumors. Anti-PD-1 is currently the most widely used immune checkpoint inhibitor, which has revolutionized cancer therapy for different types of cancer. Pembrolizumab has been approved for second-line treatment of R/M CC but has a modest overall response rate of about 15%. Therefore, multiple types of anti-PD-1 have entered clinical trials successively and evaluated the efficacy in combination with chemotherapy, targeted therapy, and immunotherapy. At the same time, the dual specific antibody of PD-1/CTLA-4 was also used in clinical trials of cervical cancer, and the results showed better than anti-PD-1 monotherapy. In addition, anti-PD-1 has also been shown to sensitize radiotherapy. Therefore, understanding the current research progress of anti-PD-1 will better guide clinical application. This review summarizes ongoing clinical trials and published studies of anti-PD-1 monotherapy and combination therapy in the treatment of cervical cancer, as well as discusses the potential molecular biological mechanisms of combination, aiming to provide the basic evidence for support anti-PD-1 in the treatment of cervical cancer and new insights in combination immunotherapy.